Euthanasia and Patient Rights in Islamic Legal Philosophy: A Critical Study of Palliative Care Practices in Muslim Countries - Halim, Patimah; Asrul, Asrul; Shuhufi, Muhammad (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
This article discusses euthanasia from the perspective of Islamic Jurisprudence. This research is normative research and is of the type of library research. The nature of the research is descriptive using comparative analysis methods. Euthanasia is quite a dilemma among doctors, legal practitioners and religious circles and is being discussed in various countries, especially Indonesia. The concept of euthanasia formulated by experts is actually prohibited in the Al-Quran and Hadith. For example, in the Qur’an in QS. Al An’am verse 151: "And do not kill a soul which Allah has forbidden (killing) except for a just cause." Killing here is defined as killing in any way, including killing with the help of another person, such as the concept of active euthanasia. Meanwhile, from a human rights perspective, euthanasia is an attempt to eliminate a human’s right to life, because the essence of euthanasia itself is eliminating human life for the reason that it will harm other people.